Treatment of suspected heat illness - Eichner, E. R. (International Journal of Sports Medicine, 1998)
1. Despite advances in the art and science of fluid balance, exertional heat illness -- even life-threatening heat stroke -- remains a threat for some athletes today. 2. Risk factors for heat illness include: being unacclimatized, unfit, or hypohydrated; certain illnesses or drugs; not drinking in long events; and a fast finishing pace. 3. Heat cramps typically occur in conditioned athletes who compete for hours in the sun. They can be prevented by increasing dietary salt and staying hydrated. 4. Early diagnosis of heat exhaustion can be vital. Early warning signs include: flushed face, hyperventilation, headache, dizziness, nausea, tingling arms, piloerection, chilliness, incoordination, and confusion. 5. Pitfalls in the diagnosis of heat illness include: confusion preventing self-diagnosis; the lack of trained spotters; rectal temperature not taken promptly; the problem of "seek not, find not;" and the mimicry of heat illness. 6. Heat stroke is a medical emergency. Mainstays of therapy include: emergency on-site cooling; intravenous fluids; treating hypoglycemia as needed; intravenous diazepam for seizures or severe cramping or shivering; and hospitalizing if response is slow or atypical. 7. The best treatment is prevention. Tips to avoiding heat illness include: rely not on thirst; drink on schedule; favor sports drinks; monitor weight; watch urine; shun caffeine and alcohol; key on meals for fluids and salt; stay cool when you can; and know the early warning signs of heat illness.